A systematic epidemiological trends analysis study in global burden of multiple myeloma and 29 years forecast - Qianru Hou; Xinyang Li; Huanxin Ma; Di Fu; Aijun Liao (Scientific Reports)
Abstract Multiple myeloma is a prevalent hematologic cancer. This investigation analyzes the latest global, regional, and national data from the Global Burden of Diseases, Injuries, and Risk Factors Study 2021. Data on the incidence, prevalence, disability-adjusted life years, and mortality rates of multiple myeloma, including estimates and 95% uncertainty intervals, were sourced from the 2021 Global Burden of Diseases Study. Furthermore, we explored the trends affecting the multiple myeloma burden from 1990 to 2021, breaking it down by demographic, age, and epidemiological factors. By 2021, the global incidence of multiple myeloma involved 148,754.63 reported cases, with confidence intervals ranging from 131,780.43 to 162,049.23. Worldwide, the number of mortality attributed to multiple myeloma reached 116,359.63, with the confidence interval lying between 103,078.62 and 128,470.57, and an age-standardized mortality rate of 1.37 per 100,000 individuals, the confidence interval for which was 1.22 to 1.52. There was a consistent increase in the incidence, prevalence, and disability-adjusted life years associated with multiple myeloma. Most of the disease burdens were seen in high income countries though its incidence is on the rise in low-income countries. Forecast for the years 2022–2050 showed the further increase in the incidence, prevalence, disability-adjusted life years, and age-standardized death rates of multiple myeloma.